IMF Survey, Volume 32, Issue 21. (IMF Survey; IMF Survey, 2003)
On November 17, Timothy Geithner took over as head of the Federal Reserve Bank of New York after serving for two years as Director of the IMF's Policy Development and Review Department. Before that, he worked from 1988 to 2001 in the U.S. Treasury, including as Under Secretary for International Affairs. He spoke with Laura Wallace about the IMF's strengths and weaknesses, and lessons on managing and resolving crises.